Occupation-specific recruitment: An empirical investigation on job seekers’ occupational (non-)fit, employer image, and employer attractiveness - Gilch, Phyllis Messalina (Frontiers in Psychology, 2022)
Organizations may need to attract occupational groups they did not recruit so far to implement strategic changes (e.g., digital transformation). Against the backdrop of this practical problem, this study introduces and explores an occupation-based measure of person-organization fit: occupational fit. I investigate its relationship with employer attractiveness based on human capital theory and explore the role of employer image as a moderator in this relationship. I surveyed 153 software engineers and mechanical engineers to analyze whether their occupational fit with software engineering and mechanical engineering firms is related to employer attractiveness. I find that occupational fit is only related to a firm’s employer attractiveness among software engineers. Employer image does not moderate this relationship. A qualitative follow-up study proposes first explanations for the unexpected differences between the two occupations by indicating that occupations may differ in the logic they apply to determine fit and their degree of professionalization. The study contributes to research by highlighting the neglected role of occupation in recruitment research and exploring potential boundary conditions of recruitment for fit. Implications for future research and practice are discussed.